Jean-Luc Nancy’s Notion of Singularity - Listik, Yonathan (Ekstasis: Revista de Hermenêutica e Fenomenologia, 2019)
My article aims to explore Nancy’s notion of sense as a key ontological concept because I believe this concept as it appears mainly in his "Sense of the World", opens the possibility of a more profound understanding of his thesis. This will not be an attempt to draw a map or a line in Nancy’s theory placing sense either as the starting point or as his central concept. Instead, it is an attempt to show that sense plays a significant role in Nancy’s understanding of singularity and finitude and therefore provide an insight into Nancy’s overall theory of being. My argument analyses sense’s centrality to Nancy´s discussion on touch and the vital role touch has in the articulation between his comprehension of mitsein/etre-avec and his elaboration of being as singular plural.